Application of Problem Based Learning on Linear Program to Analysis Rationalism Value as A Mathematics Values - Agustini, Endang Sri; Aisyah, Nyimas (Universitas Maritim Raja Ali Haji, 2024)
Rationalism value is closely related to mathematics because it is based on reason and knowledge. The results of rationalism values develop students' skills in terms of reasoning, expressing and defending their opinions, interpreting data obtained from experiences and attempting to make predictions. Therefore, this study aims to describe student rationalism values in linear program problem-based learning. The research subjects were determined purposively based on the result of summative assessment, teacher recommendation, the diversity of answers, and the willingness to be involved in the research. The selected subject was three students of class X SMA in Indralaya. The data were collected using tests and interviews, which were analyzed descriptively. The Problem-based Learning Model can bring out Rationalism Values in Linear Program material. Students can develop indicators, investigate the truth, and conclude. The indicators that appear most frequently are investigating the truth. Difficulties often predominantly arise when translating problems into mathematical models. The cause of students experiencing errors in concluding is due to errors in understanding mathematical concepts in the form of inequality signs where students mistakenly differentiate between the inequalities